Soil bacteria and protists show different sensitivity to polycyclic aromatic hydrocarbons at controlled chemical activity. Issue 17 (9th October 2019) - Winding, Anne; Modrzyński, Jakub Jan; Christensen, Jan H; Brandt, Kristian K; Mayer, Philipp
ABSTRACT: This study linked growth inhibition of soil bacteria and protists to the chemical activity ( a ) of polycyclic aromatic hydrocarbons (PAHs) and compared the sensitivities of bacteria and protists. Passive dosing from pre-loaded silicone provided well-defined and constant a of PAHs in independent tests. Single-species growth inhibition with two bacterial ( Pseuodomonas fluorescens DR54 and Sinorhizobium meliloti ) and two protist ( Cercomonas longicauda and Acanthamoeba castellanii ) strains at maximum a ( a max ) of nine and four PAHs, respectively, showed no inhibition of PAHs with a max below 0.1 (pyrene and anthracene), while growth inhibition was observed for PAHs with a max above 0.1 (e.g. fluorene, fluoranthene and naphthalene). The bacteria were less sensitive than the protists. Soil bacterial community-level growth inhibition by naphthalene was in good agreement with single-species data, but also indicated the presence of sensitive bacteria that were inhibited by a below 0.05 and increasing pre-exposure time giving higher inhibition. The a of 50% inhibition (E a 50 ) was 0.434 and 0.329 for 0.5 and 4 h pre-exposure time, respectively. Invertebrates tended to be more sensitive than single-celled organisms tested here. This suggests that PAH exposure leads to differential toxicity in soil biota, which may affect soil food web structure and cycling of organic matter. Abstract : Soil bacteria and protists were exposed to polycyclic aromatic hydrocarbons (PAHs) using passive dosing, showing protists being more sensitive than bacteria and thus differential PAH toxicity among soil microbiota.